Science book - Farndon, John (Dorling Kindersley, 2014)
Explores the history of science, how scientists have sought to explain our incredible universe and how amazing scientific discoveries have been made. This book helps you discover how Galileo worked out his scientific theories of motion and inertia, why Copernicus' ideas were contentious and what the discovery of DNA meant